Transplantation of BDNF Gene Recombinant Mesenchymal Stem Cells and Adhesive Peptide-modified Hydrogel Scaffold for Spinal Cord Repair - Li, Li-Ming; Huang, Ling-Ling; Jiang, Xin-Chi; Chen, Jia-Chen; OuYang, Hong-Wei; Gao, Jian-Qing (Current gene therapy, 2018)
Mesenchymal Stem Cells (MSCs) are promising candidates for nerve tissue engineering. Brain Derived Neurotrophic Factor (BDNF) secreted by MSCs can function to increase neural differentiation and relieve inflammation response. Gene transfection technology is an efficient strategy to increase the secretion levels of cytokines and enhance cellular functions. However, transfection and in vivo gene expression of environmentally sensitive stem cells have been one of the most challenging subjects due to the requirement in both safety and transfection efficiency. In this study, gene transfection technology was applied to prepare BDNF gene recombinant MSCs based on our previously reported liposomal vector ScreenFect® A. To improve cellular survival and gene expression after in situ implantation of MSCs, an adhesive peptide modified hydrogel scaffold was constructed using hyaluronic acid. The scaffold was optimized and modified with an adhesive peptide PPFLMLLKGSTR. The transfected MSCs exhibited improved cellular survival and sustained gene expression in the three-Dimentional (3D) scaffold in vitro. Compared to untransfected MSCs, gene recombinant MSCs effectively improved spinal tissue integrity, inhibited glial scar formation and alleviated inflammatory response. These effects were found discounted when cells were implanted without the scaffold. The study developed a promising implantation system for therapy of severe spinal cord injury and provided the first understanding of Screenfect® A about its functions on stem cell therapy for nerve tissue repair as well as three-dimentional gene expression.